Characterization of a plutonium–beryllium neutron source. (January 2021) - Söderström, P.-A.; Matei, C.; Capponi, L.; Açıksöz, E.; Balabanski, D.L.; Mitu, I.-O.
Abstract: Here we present an investigation of a plutonium–beryllium neutron source available at the Horia Hulubei National Institute of Physics and Nuclear Engineering, Romania, to be used for detector characterization during the implementation of the Extreme Light Infrastructure – Nuclear Physics project. Using several different techniques and instruments, we have measured the isotopic composition for plutonium to be 75% 239 Pu and 24% 240 Pu, with a minor contribution from other isotopes. Furthermore, we have measured the source activity as of November 20th 2019 to be 2 . 220 ( 5 ) × 1 0 5 neutrons per second with a mean energy of 3.25(17) MeV. We have also measured both the γ -tagged and full neutron energy spectra, and discuss the origin of the observed structure in the neutron energies based on these. All these parameters are of importance both for traceability of nuclear material, radioprotection, and accurate detector characterization. Highlights: A plutonium–beryllium source was found to contain 0.38 g of Pu-239. The isotopic ratio of Pu-239 to Pu-240 was 75% and 24%. Total activity of the source was 222000 n/s with a mean neutron energy of 3.25 MeV. The γ -ray coincident neutron spectrum has three peaks at 2 MeV, 3.5 MeV and 5 MeV. The full neutron energy spectrum shows peak-like features at 7 MeV and 9 MeV.